Redescription of the genus Chlamydolecanium Goux, 1933 (Hemiptera: Coccoidea: Coccidae) with a discussion of its affinities - Vea, Isabelle M. (Zootaxa, 2011)
The monotypic genus Chlamydolecanium Goux (Hemiptera: Coccoidea: Coccidae) is known only from the original collection in Corsica. The original description does not allow definite placement in any of the subfamilies in the Coccidae. Although it had been suggested that it belonged to the Cardiococcinae, no other members of this subfamily were geographically close. The adult female and 1 st -instar nymph of the type species, Chlamydolecanium conchioides Goux are here redescribed. A parsimony analysis was undertaken based on 56 morphological characters of the adult females in 29 taxa (24 genera considered to belong to the Cardiococcinae, plus Parafairmaria bipartita (Signoret), an incertae sedis monospecific genus possibly close to Cardiococcinae, plus the recently described Kenima galilit Ben-Dov plus two other soft scale genera as outgroups (Coccus hesperidum L. and Paralecanium frenchii (Maskell)). This analysis confirmed the placement of the genus Chlamydolecanium within the Cardiococcinae clade, although its sister-group relationships remain unresolved. Its geographic distribution and taxonomic relationships are discussed.